Mitochondrial Effects on Seeds of Cancer Survival in Leukemia - El-Shaqanqery, Hend E.; Mohamed, Rania Hassan; Sayed, Ahmed A. (Frontiers in Oncology, 2021)
The cancer metabolic alteration is considered a hallmark and fast becoming road for therapeutic intervention. Mitochondria have been regarded as essential cell elements that fuel the metabolic needs of most cancer cell types. Leukemia stem cells (LSCs) are heterogeneous, highly self-renewing and pluripotent cell population within leukemic cells. The most important source of ATP and metabolites to fulﬁll the bioenergetics and biosynthetic needs of most cancer stem cells are mitochondria. In addition, mitochondria have core role in autophagy and cell death, and are the main source of reactive oxygen species (ROS) generation. Overall, the growing evidence now shows that mitochondrial activities and pathways have changed to adapt with different types of leukemia, thus mitochondrial metabolism could be centered for blood malignancies therapy. This review focuses on the function of mitochondria in LSC of the different leukemia types.